2018
DOI: 10.48084/etasr.2376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Improper Curing on the Properties of Normal Strength Concrete

Abstract: In real applications, 28 days are regarded as proper curing time for concrete. There is a self-evident need to minimize the duration of curing days. For this purpose, this research investigates 1 to 7 days of curing and compares it with concrete cured for 28 days. Three grades of normal concrete strength grade 30, grade 35 and grade 40 were made. After curing, two exposure conditions were applied to the concrete, inside laboratory-controlled environment and outside environment. Results indicate that slump incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…As a result, the dry density of foamed concrete increase with the increase of curing days. This finding is true according to previous research that has been conducted that found water loss from concrete decreases with increasing curing days (Memon, Sam, Awang & Memon, 2018).…”
Section: Density Of the Samplesupporting
confidence: 82%
“…As a result, the dry density of foamed concrete increase with the increase of curing days. This finding is true according to previous research that has been conducted that found water loss from concrete decreases with increasing curing days (Memon, Sam, Awang & Memon, 2018).…”
Section: Density Of the Samplesupporting
confidence: 82%
“…As a result, the technique has been readily introduced where water-filled internal curing agents acting as reservoirs are added to the concrete mixture which will gradually release water during hydration and evaporation process [31][32][33][34], as illustrated in Figure 2. High-performance concrete (HPC) mixtures were initially developed given the growing issues regarding concrete durability [35,36] and due to the use of lower water-cementitious (w/c) material ratios, in addition to chemical admixtures and supplementary cementitious material (SCMs). Measuring the extent of hydration in the cementitious system is a key indicator that leads towards achieving the good performance of the concrete [37].…”
Section: Self-curing Agent and Mechanism In Cementitious Materialsmentioning
confidence: 99%
“…Prewetted lightweight aggregates have often been used as internal reservoirs in which a system of capillary pores in cement paste is formed during hydration, and as soon as the relative humidity (RH) decreases (due to hydration and drying), a humidity gradient develops [35,[60][61][62]. The migration of water in concrete based on the law of fluid flow and the system's law of capillary attraction is illustrated in Figure 5.…”
Section: Artificial Lightweight Aggregate (Lwa)mentioning
confidence: 99%
“…50 • F is not acceptable [5]. The improper curing of concrete can result in loss of half of its strength and proper curing of concrete ensures 90% attainment of concrete strength [6]. For proper curing, adequate moisture and temperature should be provided to concrete [5].…”
Section: Introductionmentioning
confidence: 99%
“…Curing not only reduces the shrinkage and permeability loss, but it also protects it from strength and durability losses, essentially on early days of strength gain [5]. The prime purpose of concrete curing in early age is to provide concrete enough amount of water for strength gains [6]. Based on conditions and availability, various methods for concrete curing are employed such as curing with gunny bags, curing with potable water, air curing, polythene curing, steam curing, ponding, sprinkling, wet covering etc.…”
Section: Introductionmentioning
confidence: 99%